노인의 장애 및 주관적 건강의 남녀차이와 사회경제적 요인의 영향 - 전경숙; 장숙랑; 이선자; Jeon, Gyeong-Suk; Jang, Soong-Nang; Rhee, Seon-Ja (Journal of preventive medicine and public health, 2009)
Objectives : Research on the gender differences of health among older Korean people has been limited compared with the research for other stages of life. This study first examined the patterns and magnitude of the gender differences of health in later life. Second, we examined the gender differences in the health of older men and women that were attributable to differing socioeconomic conditions. Methods : Using the nationally representative 2005 Korean National Health and Nutrition Examination Survey, the gender differences in disability and subjective poor health were assessed by calculating the age adjusted and gender-specific prevalence. Logistic regression analyses were used to assess if the differences between the men and women for health could be explained by differential exposure to socioeconomic factors and/or the differential vulnerability of men and women to these socioeconomic factors. Results : Our results indicated that older women were more likely than the men to report disability and poor subjective health. The health disadvantage of older women was diminished by differential experiences with socioeconomic factors, and especially education. The differences shrink as much as 43.7% in the case of disability and 35.4% in the case of poor subjective health by the differential exposure to educational attainment. Any differential vulnerability to socioeconomic factors was not found between the men and women, which means that socioeconomic factors may have similar effect on health in both genders. Conclusions : Differential socioeconomic experience and exposure between the men and women might cause gender difference in health in old age Koreans.